2018
DOI: 10.1253/circj.cj-17-1202
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Energy Intake as Predictors of Functional Status After Cardiac Rehabilitation in Elderly Inpatients With Heart Failure ― A Retrospective Cohort Study ―

Abstract: MNA-SF score and total energy intake at the commencement of CR are novel predictors of the extent of functional recovery of elderly HF inpatients after in-hospital CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…The high pooled prevalence of malnutrition and risk of malnutrition according to MNA confirm earlier findings from a meta-analysis with slightly higher pooled prevalence (95% CI) of 29% (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) for malnutrition and 49% (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) for risk of malnutrition [83]. However, heterogeneity was high, which limits the interpretation of these results.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The high pooled prevalence of malnutrition and risk of malnutrition according to MNA confirm earlier findings from a meta-analysis with slightly higher pooled prevalence (95% CI) of 29% (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) for malnutrition and 49% (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) for risk of malnutrition [83]. However, heterogeneity was high, which limits the interpretation of these results.…”
Section: Discussionsupporting
confidence: 81%
“…Seven [31,33,34,69,76,81,82] out of ten studies reported a significant association between either low MNA or low MNA-SF and low BI or low FIM. One study [30] did not show an association and in two studies [54,64] heterogeneous outcomes were observed. Higher BMI values (in the normal to overweight range) were significantly associated with higher scores of the BI [68] and the FIM [64] in one study each.…”
Section: Association Between Nutritional Status and Functional Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of malnutrition in the present study is higher than that reported in most healthcare settings [ 19 , 20 , 21 ]. In contrast, other studies that analyzed hospital-deconditioned older patients reported higher levels of malnutrition, similar to the present research [ 42 , 43 ]. This difference may be due to the tool used to define malnutrition.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with HF who were at risk of malnutrition experienced worse physical function. (Matsuo et al., 2019) Furthermore, malnutrition independently predicted the functional dependence of patients with HF after cardiac rehabilitation (Katano et al., 2018). In addition, functional status was also associated with depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%